Pancreatic Panniculitis – case report - Tavares, Ermelindo Silva; Parente, Joana Alexandra Devesa; Vera-Cruz, Frederico Pinto; Lima, José Nunes; Aranha, João Manuel Pires; Estrela, António Pedro Fernandes (Revista Portuguesa de Cirurgia, 2010)
A 65-years-old female admitted on general surgery with acute pancreatitis, complicated with painful, erythematous and subcutaneous nodules, located on the legs, followed by poliarthritis. The combination of clinical and laboratory data as well as the results of skin biopsy confirmed the diagnosis of pancreatic panniculitis. The patient was treated with conservative therapy only led to her underlying pathology. A successful outcome and disappearance of the lesions were registered. Pancreatic panniculitis is a rare disorder that affects a small number of patients with pancreatic disorders, particularly pancreatitis (acute and chronic) and carcinoma of the pancreas. The disease is characterized by necrosis of subcutaneous adipose tissue and manifests itself usually by subcutaneous, erythematous and painful nodules, located preferentially on the lower limbs, and in more than half of the cases, there is inflammation of the periarticular fat. In the most cases, histopathology reveals lobular panniculitis and fat cells without nuclei (ghost cells). Treatment is conservative, aimed at the underlying pathology. Keywords: acute pancreatitis, pancreatic carcinoma, panniculitis, ghost cells.